The use of conditional convergence between economies to estimate steady state incomes within economies - DelVecchio, Micah, author; Cutler, Harvey, advisor; Tavani, Daniele, committee member; Braunstein, Elissa, committee member; Costanigro, Marco, committee member (Colorado State University. Libraries, 2014)
This dissertation introduces a panel data method to estimate country-specific steady state levels of output in an augmented Solow growth model. The use of panel data permits the estimation of a country-specific effect which can explain the surprising result that many developing economies are above their steady states. These empirical results also confirm that the augmented Solow model can explain the present cross-country income divergence of developed and developing economies. Another application finds evidence that the post-Soviet economies began their transition toward markets with initial conditions of overcapitalization. Finally, when the results are sufficient, there is also the possibility of describing an entire period of growth and gaining insights into future periods. This is shown with the OECD economies. In Islam (1995), panel data is first used to estimate the parameters of the Solow growth model. The following year, Cho and Graham (1996) published a small paper which illustrates a simple way to compute steady state levels of per capita income by using the results of cross-sectional convergence tests. This dissertation simply combines these two methods with the result that the interpretations are more satisfying. In sum, we find that countries can begin a period of development above or below their steady states and that countries converging from above should be considered to be overcapitalized. This implies that development through investment can only succeed when there is convergence from below the steady state. Above the steady state, total factor productivity is too low to sustain the relatively high levels of capital. The organization of the dissertation is linear with an introduction preceding the second chapter's literature review and the development of a theoretical and empirical model in the third chapter. The applications of the method then follow. Chapter 4 uses a worldwide sample to compare the result to other work and to show that this fundamental model of growth theory can explain the observed increasing levels of international inequality. Chapter 5 takes a look at the transition economies. In addition to finding evidence of overcapitalization, this dissertation finds a positive correlation between growth and the privatization of small business under transition. Additionally, there is a negative impact of price liberalization under the conditions of repressed inflation experienced by many Soviet-era planned economies. Chapter 6 uses a sample of OECD economies to obtain a significant deterministic, technological growth rate. This is possible because the countries are similar enough to make the assumption that they have the same growth rate more realistic. This enables an understanding of steady states after the initial period and leading into the most contemporaneous period of the sample.
Keywords: institutions; growth; panel; development; econometrics